Lecturer Capacity Building in Developing Video-Based Learning Media - Risdianto, Eko; Marlina, Yessi; Mulyani, Sri; Fitri, Fitri; Roziana, Roziana; Restusari, Lily (Asosiasi Profesi Multimedia Indonesia, 2023)
The community service aims to increase the capacity of lecturers in developing video-based learning media. The service method is carried out through training activities. The target of the service is the Nutrition Department Lecturers of the Riau Ministry of Health Polytechnic. As many as 14 Nutrition Lecturers were involved in the training which was held in July 2023. The research instrument used was a closed sheet with four answer choices. Analysis of the training participants' responses to the training activities for making learning videos was carried out using descriptive statistical analysis. This is done by processing the proportion of data from filling in the responses by the training participants. Percentages are obtained based on modified Likert Scale calculations. The results showed that as many as 14 respondents or 100% of the respondents were in the category of strongly agreeing with the statements that led to a positive response from the trainees to the training activities that had been carried out. Follow-up workshops on creating innovative learning videos are urgently needed to acquire new skills for Teachers/Lecturers of the Department of Nutrition at the Riau Ministry of Health Polytechnic.